IL-12 Expressing oncolytic herpes simplex virus promotes anti-tumor activity and immunologic control of metastatic ovarian cancer in mice. Issue 1 (December 2016) - Thomas, Eric; Meza-Perez, Selene; Bevis, Kerri; Randall, Troy; Gillespie, G.; Langford, Catherine; Alvarez, Ronald
Abstract Background Despite advances in surgical aggressiveness and conventional chemotherapy, ovarian cancer remains the most lethal cause of gynecologic cancer mortality; consequently there is a need for new therapeutic agents and innovative treatment paradigms for the treatment of ovarian cancer. Several studies have demonstrated that ovarian cancer is an immunogenic disease and immunotherapy represents a promising and novel approach that has not been completely evaluated in ovarian cancer. Our objective was to evaluate the anti-tumor activity of an oncolytic herpes simplex virus "armed" with murine interleukin-12 and its ability to elicit tumor-specific immune responses. We evaluated the ability of interleukin−12-expressing and control oncolytic herpes simplex virus to kill murine and human ovarian cancer cell lines in vitro. We also administered interleukin−12-expressing oncolytic herpes simplex virus to the peritoneal cavity of mice that had developed spontaneous, metastatic ovarian cancer and determined overall survival and tumor burden at 95 days. We used flow cytometry to quantify the tumor antigen-specific CD8+ T cell response in the omentum and peritoneal cavity. Results All ovarian cancer cell lines demonstrated susceptibility to oncolytic herpes simplex virus in vitro. Compared to controls, mice treated with interleukin−12-expressing oncolytic herpes simplex virus demonstrated a more robust tumor antigen-specific CD8+ T-cell immune response in the omentum (471.6 cells vs 33.1 cells;p = 0.02) and peritoneal cavity (962.3 cells vs 179.5 cells;p = 0.05). Compared to controls, mice treated with interleukin−12-expressing oncolytic herpes simplex virus were more likely to control ovarian cancer metastases (81.2 % vs 18.2 %;p = 0.008) and had a significantly longer overall survival (p = 0.02). Finally, five of 6 mice treated with interleukin−12-expressing oHSV had no evidence of metastatic tumor when euthanized at 6 months, compared to two of 4 mice treated with sterile phosphate buffer solution. Conclusion Our pilot study demonstrates that an interleukin−12-expressing oncolytic herpes simplex virus effectively kills both murine and human ovarian cancer cell lines and promotes tumor antigen-specific CD8+ T-cell responses in the peritoneal cavity and omentum, leading to reduced peritoneal metastasis and improved survival in a mouse model.